2019
DOI: 10.3390/ijgi8060260
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Police Officers’ Perception of Hotspots: What Can Be Done to Improve Officer’s Situational Awareness?

Abstract: The idea behind patrol activity is that police officers should be the persons best acquainted with the events and people in their patrol area. This implies that they should have access to relevant data and information (e.g., where and how to pay attention, when and how crimes are committed) in order to effectively perform their police duties. To what extent their perceptions of the places prone to crime (hotspots) are accurate and what the implications are for police efficiency if they are incorrect is an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…On the other hand, there has been a vast amount of research focusing purely on analysing and exploring patterns in recorded crime data [7][8][9][10][11][12][13][14][15][16][17][18][19] relating to the time of day and land use. This research combines the perceived crime data with recorded crime data in one analysis in order to explore the attributes of various parts of the selected city-Ostrava, Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there has been a vast amount of research focusing purely on analysing and exploring patterns in recorded crime data [7][8][9][10][11][12][13][14][15][16][17][18][19] relating to the time of day and land use. This research combines the perceived crime data with recorded crime data in one analysis in order to explore the attributes of various parts of the selected city-Ostrava, Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that the larger a population is, the higher the number of crimes will be [7,49,53], and a population density is also related to increased police presence. Police patrol activity can be very dynamic [54], and coinciding crime hotspots with the presence of police units may be indicative of police organization to tackle crime. However, this situation could also indicate that most police work does not focus on crime reduction but rather on respond to emergency situations [55].…”
Section: Discussionmentioning
confidence: 99%
“…A similar methodology for a perception-based study has been used in community and farmer’s perception studies (Shukla et al , 2018; Semenza et al , 2008; Vedwan and Rhoades, 2001; Tripathi and Singh, 2013). However, limited research (Ilijazi et al , 2019; Gupta et al , 2018; Nirupama and Etkin, 2012) is available on the perception of government officials, authorized for vital decisions on a regular basis that influences developmental planning and policies as they relate to climate change-induced disasters. Although the samples size of 41 represents a small proportion of the State Government officials, it does account for diverse age groups, varied work experiences and affiliation to different departments (Table 1).…”
Section: Methodsmentioning
confidence: 99%